Biochemical predictors of diabetic foot osteomyelitis: A potential diagnostic role for parathormone. Issue 1 (24th November 2022) - Caruso, Paola; Maiorino, Maria Ida; Scappaticcio, Lorenzo; Porcellini, Chiara; Matrone, Rita; Cirillo, Paolo; Macera, Margherita; Gicchino, Maurizio; Vietri, Maria Teresa; Bellastella, Giuseppe; Coppola, Nicola; Esposito, Katherine
Abstract: Aims: The aims of this study were to evaluate parathormone (PTH) levels in people with diabetic foot ulcers (DFU) and investigate the relationship between PTH levels and osteomyelitis (OM) in this population. Materials and Methods: Eighty‐eight patients were admitted for DFU in a tertiary‐care centre from October 2021 to May 2022. OM was diagnosed by clinical, laboratory, and radiological evaluations. Laboratory measurements and clinical parameters were collected from medical records. Participants in the study were divided into two groups according to the diagnosis of OM (patients with OM, group 1 [ n  = 54] and patients without OM, group 2 [ n  = 34]). Results: Compared with group 2, patients in group 1 were younger and had a longer duration of diabetes. Erythrocyte sedimentation rate and fibrinogen were significantly higher in group 1 compared with group 2. PTH levels were significantly lower (group 1 vs. group 2, median [interquartile range] 16.2 (11.6, 31.0) vs. 23.7 (17.0, 38.1), p  = 0.008) and alkaline phosphatase was significantly higher (97.0 (79.0, 112.0) vs. 88.0 (63.0, 107.0), p  = 0.031) in group 1. In multiple linear regression analysis, the only independent predictors of PTH concentrations were alkaline phosphatase levels (β‐coefficient 0.441, p  < 0.001) and the presence of OM (β‐coefficient −0.290, p  = 0.038). Conclusions: In a population of patients with diabetes and OM admitted to a tertiary university centre, PTH levels were lower as compared with diabetic individuals without OM. The OM and alkaline phosphatase levels were independent predictors of PTH levels in this selected population.